2010
DOI: 10.4049/jimmunol.0901843
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Promotes NK Cell Production of IL-17 during Toxoplasmosis

Abstract: Previous studies have implicated T cell production of IL-17 in resistance to T. gondii as well as the development of immune mediated pathology during this infection. Analysis of C57BL/6 and C57BL/6 RAG-/- mice challenged with T. gondii identified NK cells as a major innate source of IL-17. The ability of soluble toxoplasma antigen to stimulate NK cells to produce IL-17 was dependent on the presence of accessory cells and the production of IL-6, IL-23 and TGF-β. In contrast, these events were inhibited by IL-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
137
2
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(154 citation statements)
references
References 66 publications
9
137
2
4
Order By: Relevance
“…In contrast, lack of IL-23 had no effect on the development of experimental asthma in mice (34). The latter study is in line with our results, whereas IL23p19 (46), and NK cells (47). In our setting, mice with pIC-triggered exacerbation of experimental asthma displayed markedly increased numbers of IL-17-producing NK cells.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, lack of IL-23 had no effect on the development of experimental asthma in mice (34). The latter study is in line with our results, whereas IL23p19 (46), and NK cells (47). In our setting, mice with pIC-triggered exacerbation of experimental asthma displayed markedly increased numbers of IL-17-producing NK cells.…”
Section: Discussionsupporting
confidence: 81%
“…IL-17A and IL-17F are both produced by memory T helper cells, in particular Th17 cells, but also by CD8ϩ, ␥/␦ϩ, and natural killer T cells. Recent studies have demonstrated innate sources of IL-17A, as well as production of IL-17A by tissue-specific cells, such as Paneth cells (14)(15)(16)(17). Both cytokines can be excreted as homodimers or as IL-17A/F heterodimers (18,19).…”
mentioning
confidence: 99%
“…In the absence of cNK cells, impaired priming of CD4 + and CD8 + T cells was observed [50]. Recently, cNK cells have also been identified as a major source of IL-17 during T. gondii infection, a cytokine that confers resistance to this pathogen [51]. In contrast to what has been seen for C. rodentium, IL-22 has pathogenic roles during T. gondii infection, causing destruction of intestinal tissue integrity [52,53].…”
Section: Cnk Cellsmentioning
confidence: 70%